Challenges for the management of the invasive blackberry (Rubus niveus) in the restoration of the Scalesia forest in the Galapagos Islands. (22nd March 2021) - Renteria, Jorge L.; Atkinson, Rachel; Crespo, Claudio; Gardener, Mark R.; Grosholz, Edwin D.
Abstract: Strong competitive ability of introduced plant species has been frequently stated as a key factor promoting successful invasion. The dynamics of invasive species may depend on their abilities to compete for resources and exploit disturbances relative to native species. This study compares the growth performance of the invasive blackberry ( Rubus niveus Thunb.) with four of the most common woody native species of the Scalesia forest in the Galapagos Islands. Using a series of greenhouse and field studies, the growth rate and biomass production of native species alone and in competition with R. niveus was compared under different water and light stress conditions. Rubus niveus showed a faster growth rate and biomass production than the native species as well as a broad tolerance to light and water stress conditions. Competitive ability was also assessed by looking at the seedbank and regeneration processes after herbicide control in the field. Although the number of R. niveus seedlings that germinated from the soil samples was considerably larger than that of native species, recruitment of the invasive on the experimental plots was limited. Overall, R. niveus showed superior competitive ability over native species with comparable growth forms, suggesting a possible mechanism that enables R. niveus to successfully invade a wide range of habitats in the Galapagos Islands. Implementing an integrated management strategy including biological control, seedbank reduction, and active revegetation, should improve the efficiency of R. niveus management, enabling the restoration of degraded vegetation in the Galapagos.